Epidemiological profile of health consultations during the Mozambique 9(th) National Cultural Festival, August 2016 - Braga, Judite Monteiro (Pan Afr Med J, 2019)
INTRODUCTION: The use of mass gatherings as spaces to practice health surveillance has been growing in recent years. In Mozambique, the 9th National Festival of Culture in 2016 was selected for this practice. A specific public health surveillance system to facilitate rapid detection of outbreaks and other health-related events was implemented for this event with real time data collection and analysis METHODS: A descriptive epidemiological evaluation of all the health consultations that occurred in fixed posts prepared for the event was conducted. The data were collected through electronic mobile system (tablets) in real time, with the aid of a form designed for this purpose and sent directly to the incident command system (ICS) RESULTS: During the event, a total of 355 patients were assisted, 52.3% were female, 87.0% were from Beira city and the artists were the group that most frequently sought health care at 59.4%. The largest number of visits took place on the third day (36.4%). People over 45 years of age were the age group that most frequently sought health care (30.8%). The main provisional diagnoses of those who were attended to during the festival was arterial hypertension (20.3%), followed by febrile syndrome (19.0%), with falls being the most frequent causes of trauma during the festival (60.0%). CONCLUSION: The system of monitoring in real time using mobile technologies proved to be efficient for the monitoring of the main health events during the mass gatherings. This profile of health consultations encourages the health sector to plan strategies and actions geared to the reality of care for this type of event.